2010
DOI: 10.1038/mp.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a genome-wide supported psychosis risk variant on neural activation during a theory-of-mind task

Abstract: Schizophrenia is associated with marked deficits in theory of mind (ToM), a higher-order form of social cognition representing the thoughts, emotions and intentions of others. Altered brain activation in the medial prefrontal cortex and temporo-parietal cortex during ToM tasks has been found in patients with schizophrenia, but the relevance of these neuroimaging findings for the heritable risk for schizophrenia is unclear. We tested the hypothesis that activation of the ToM network is altered in healthy risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 70 publications
(94 reference statements)
13
141
3
1
Order By: Relevance
“…[33][34][35] As expected, we observed significant association of rs2709370 with hippocampal function during memory recall (P<0.01, family wise error corrected for multiple comparisons across the region of interest, Figure 2). The risk allele [C] carriers likewise showed diminished activation of the left hippocampus, consistent with a previous study of patients with BD who showed impaired hippocampal function, further supporting the involvement of CREB1 in BD.…”
Section: Effects Of the Risk Snps On Hippocampal Volumes And Hippocamsupporting
confidence: 50%
See 1 more Smart Citation
“…[33][34][35] As expected, we observed significant association of rs2709370 with hippocampal function during memory recall (P<0.01, family wise error corrected for multiple comparisons across the region of interest, Figure 2). The risk allele [C] carriers likewise showed diminished activation of the left hippocampus, consistent with a previous study of patients with BD who showed impaired hippocampal function, further supporting the involvement of CREB1 in BD.…”
Section: Effects Of the Risk Snps On Hippocampal Volumes And Hippocamsupporting
confidence: 50%
“…30,31 We extracted the association results of CREB1 SNP with bilateral hippocampal volume instead of single-side hippocampal volume from these two GWASs, because the volumes of the right and left hippocampus do not differ significantly in healthy subjects, 31 and the genetic bases are likely the same. 32 For brain functions, we analyzed the data of a German sample of healthy individuals (N = 279) that was part of an ongoing study on neurogenetic mechanisms of psychiatric disease to study the effects of risk CREB1 SNPs on hippocampal function, [33][34][35] using blood oxygenation level-dependent functional magnetic resonance imaging measurement during three consecutive blocks of memory tasks (that is, encoding, recall and recognition of faceprofession pairs). We analyzed the effects of the SNPs on right and left hippocampal function separately, assuming potential asymmetry in hippocampal function, with the right hippocampus supporting processes contributing to visuo-spatial memory and the left hippocampus to verbal/narrative or episodic memory.…”
Section: Analysis Of Hippocampal Volume Hippocampal Function and Cogmentioning
confidence: 99%
“…Four studies including ours (Donohoe et al, 2011;Walters et al, 2010;Hashimoto et al, 2010) that enrolled both patients and controls consistently found no significant contributions of this SNP to cognitive function in controls, although they all found significant results in patients. Interestingly, there are at least six studies that enrolled controls only and found significant results (Lencz et al, 2010;Balog et al, 2011;Esslinger et al, 2009;Esslinger et al, 2011;Voineskos et al, 2011;Walter et al, 2011). Five of these studies, however, were imaging genetic studies using intermediate phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Using cognitive intermediate phenotypes or other related neurobiological intermediate phenotypes such as functional MRI or structural MRI data, many studies found that the risk allele was associated with low cognitive functions (Balog et al, 2011;Hashimoto et al, 2010) and altered cortical activity Esslinger et al, 2009;Walter et al, 2011) or volumes (Voineskos et al, 2011). By contrast, two studies in schizophrenia patients found different results (Walters et al, 2010;Donohoe et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, the following tasks were performed: (1) an associative learning task 21 , in which subjects learn and are then tested on face-job associations, (2) an n-back working memory task 22 , in which subjects are presented with a sequence of numbers and press a button corresponding either to the number currently seen (control condition, '0-back) or the number seen two presentations previously ('2-back'), (3) a theory of mind task 23 , in which subjects have to make inferences about the state of mind of a human based on a series of cartoons, (4) a flanker task 24 in which subjects have to perform or withhold a button press depending on a set of either congruent or incongruent stimuli, requiring cognitive control, (5) an implicit emotion recognition task 25 , in which subjects match pictures of angry and fearful faces, (6) a monetary reward task 26 , in which subjects receive or do not receive monetary rewards according to their performance in a reaction time task and a 5 minutes of rest period. Further information, including details of the imaging parameters, is provided in the SI…”
Section: Imaging Genetics Studymentioning
confidence: 99%